PARP-1 Is Critical for Recruitment of Dendritic Cells to the Lung in a Mouse Model of Asthma but Dispensable for Their Differentiation and Function - Laura C. Echeverri Tirado; Mohamed A. Ghonim; Jeffrey Wang; Amir A. Al-Khami; Dorota Wyczechowska; Hanh H. Luu; Hogyoung Kim; Maria Dulfary Sanchez-Pino; José Yélamos; Lina M. Yassin; A. Hamid Boulares (Mediators of Inflammation)
Dendritic cells (DCs) are critical in asthma and many other immune diseases. We previously demonstrated a role for PARP-1 in asthma. Evidence on PARP-1 playing a role in Th2-associated DC function is not clear. In this study, we examined whether PARP-1 is critical for DC differentiation and function using bone marrow progenitors and their migration to the lung in an ovalbumin-based mouse model of asthma. Results show that changes in PARP-1 levels during GM-CSF-induced DC differentiation from bone marrow progenitors were cyclic and appear to be part of an array of changes that included STAT3/STAT5/STAT6/GRAIL/RAD51. Interestingly, PARP-1 gene deletion affected primarily STAT6 and γH2AX. PARP-1 inhibition significantly reduced the migration of DCs to the lungs of ovalbumin-challenged mice, which was associated with a concomitant reduction in lung levels of the adhesion molecule VCAM-1. The requirement of PARP-1 for VCAM-1 expression was confirmed using endothelial and lung smooth muscle cells. PARP-1 expression and activity were also required for VCAM-1 in differentiated DCs. An assessment of CD11b+/CD11c+/MHCIIhigh DCs in spleens and lymph nodes of OVA-sensitized mice revealed that PARP-1 inhibition genetically or by olaparib exerted little to no effect on DC differentiation, percentage of CD80+/CD86+/CD40+-expressing cells, or their capacity to promote proliferation of ovalbumin-primed (OTII) CD4+ T cells. These findings were corroborated using GM-CSF-induced differentiation of DCs from the bone marrow. Surprisingly, the PARP-1−/− DCs exhibited a higher intrinsic capacity to induce OTII CD4+ T cell proliferation in the absence of ovalbumin. Overall, our results show that PARP-1 plays little to no role in DC differentiation and function and that the protective effect of PARP-1 inhibition against asthma is associated with a prevention of DC migration to the lung through a reduction in VCAM-1 expression. Given the current use of PARP inhibitors (e.g., olaparib) in the clinic, the present results may be of interest for the relevant therapies.